USE OF INTERNET TECHNOLOGIES FOR THE DEVELOPMENT OF SOCIAL SERVICES FOR CHILDREN WITH DISABILITIES AND THEIR FAMILIES IN THE COMMUNITY (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
Considering the processes of deinstitutionalisation and the development of social services in the community accessible for children and families, the use of Internet technologies in social work is extremely relevant. The purpose of this publication is to describe the results of research on the use of Internet technologies as a tool for the development of social services for children with disabilities and their families. In the course of the study, which was carried out between October 2016 and June 2018, we used such research methods as: theoretical research methods, document analysis, as well as individual and focused group interviews.The first objective of the research was to explore the varieties and features of services for children with disabilities in the community as an alternative to institutional care and analyze the process of services development. The formed list of services for children with disabilities and their families, which are possible in Ukraine according to the current legislation, the following groups of services were defined: (a) correction and development services; (b) educational services; (c) care services; (d) support services for families with children with disabilities. We revealed that the development of the service includes a number of practical tasks that cover the following stages: (1) determining the community's need in the service, (2) planning the implementation of the service, (3) selecting and training the specialists who will implement the service, (4) building communications with clients and developing an affiliate network, (5) monitoring the results of service implementation.The second stage of the study was conducting a theoretical analysis of the specifics of various types of Internet technologies and their use for work on development of services in community. Based on this we have developed a model for the development of social services for children with disabilities and their families in the community using Internet technologies for the activities of both social work managers and specialists who directly provide services to clients.During the empirical part of the study, we analysed experience and perspectives of application of Internet technologies by heads and managers of social organizations, as well as specialists working with children with disabilities in the provision of services. The results of the study are the first step in verifying the proposed theoretical model; they confirm that the topic of using Internet technologies is extremely relevant for the development and provision of services in Ukraine and in Europe. Domestic and foreign experts who took park in the study named the following potential Internet technologies in providing services: organization of day-care for palliative children; long-distance social support for families and children; transfer of certain elements of correctional lessons to the Internet platforms; organization of online peer support groups for parents of children; Internet technologies of virtual and augmented (mixing reality and artificial effects) reality for the correction and therapy of people with mental disorders.Comparing the responses of domestic and foreign specialists working with children with disabilities and their families, it is possible to conclude that foreign colleagues more actively use Internet technologies to perform professional tasks, both for working with clients, and for organizing and providing services, while Ukrainian specialists are limited to their use mainly for informational purposes. The study determines the peculiarities of using Internet technologies, which need to be considered, integrating such technologies into the process of providing services to children with disabilities and their families in Ukraine.
Keywords: social work, social services, Internet technologies, children with disabilities, community